마이크로웨이브 졸-겔법을 응용한 극저온 자기냉매용 HoN 분말 합성 및 자기열량효과 - 안종빈; Jong Bin Ahn; 김동수; Dongsoo Kim; 윤석영; Seog Young Yoon; 최철진; Chuljin Choi (대한금속·재료학회지, 54(4), 2016)
Rare-earth (RE) mono-nitrides can be used as magnetocaloric materials for the magnetic refrigerant for liquefying hydrogen. In this study, holmium nitride (HoN) particles were prepared by sol-gel method with microwave irradiation. HoN particles were successfully synthesized by 2-step heat treatment in N2 atmosphere form gel-type intermediate by microwave irradiation. X-ray diffraction patterns of the synthesized HoN particles exhibited the six sharp peaks in good agreement with each plane of crystallographic structure of HoN. Especially, the synthesized HoN particles reveal a high magnetic entropy change (△Sm) of 36.6 J/kgK in applied field of 5T at 14.2 K which is comparable with those of rare earth mono-nitrides by carbothermic reduction method or plasma arc discharge technique.